2002
DOI: 10.1073/pnas.082120099
|View full text |Cite
|
Sign up to set email alerts
|

Induction and acceleration of insulitis/diabetes in mice with a viral mimic (polyinosinic-polycytidylic acid) and an insulin self-peptide

Abstract: PolyIC. These studies demonstrate that ''normal'' mice have autoreactive T lymphocytes able to rapidly target islets and insulin given appropriate MHC alleles and that a peripherally administered insulin peptide (an altered peptide ligand of which is in clinical trials) can enhance specific anti-islet autoimmunity. These first PolyIC͞insulin-induced murine models should provide an important tool to study the pathogenesis of type 1 diabetes with experimental autoimmune diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 35 publications
3
102
0
5
Order By: Relevance
“…24,25 Viral myocarditis, Lyme disease, rheumatoid arthritis, multiple sclerosis, and virus-induced autoimmune diabetes are autoimmune diseases that are considered to be initiated or aggravated by immune challenge with microbial pathogens. [24][25][26][27][28] Consistent with this model, we have previously shown that a MAGE-A6-derived peptide, MAGE-A6 172-187 , and a peptide derived from the permease protein of the ubiquitous Mycoplasma penetrans HF-2 bacterium (HF-2 216-229 ) share a high-degree of structural homology and immunologic cross-reactivity in the CD4 C T-cell compartment present in a broad range of healthy donors and melanoma patients. 29 We now show that these same MAGE-A6 172-187 and HF-2 216-229 peptides can induce a cross-reactive, polyclonal CD8 C T-cell repertoire in HLA-A*0201 (HLA-A2)…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…24,25 Viral myocarditis, Lyme disease, rheumatoid arthritis, multiple sclerosis, and virus-induced autoimmune diabetes are autoimmune diseases that are considered to be initiated or aggravated by immune challenge with microbial pathogens. [24][25][26][27][28] Consistent with this model, we have previously shown that a MAGE-A6-derived peptide, MAGE-A6 172-187 , and a peptide derived from the permease protein of the ubiquitous Mycoplasma penetrans HF-2 bacterium (HF-2 216-229 ) share a high-degree of structural homology and immunologic cross-reactivity in the CD4 C T-cell compartment present in a broad range of healthy donors and melanoma patients. 29 We now show that these same MAGE-A6 172-187 and HF-2 216-229 peptides can induce a cross-reactive, polyclonal CD8 C T-cell repertoire in HLA-A*0201 (HLA-A2)…”
Section: Introductionmentioning
confidence: 64%
“…34 We had previously noted that both MAGE-A6 172-187 and HF-2 216-229 peptides were capable of stimulating MAGE-A6-specific CD4 C T-cell responses in the majority of healthy donors and melanoma patients tested, C T-cells being derived from a memory pool of donor T cells and demonstrating the ability to recognize both MAGE-A6 172-187 -pulsed target cells as well as HLA-DR-matched, MAGE-A6 C tumor cell lines. Such immunologic molecular mimicry had also previously been reported for a peptide derived from the herpes simplex virus type 1 glycoprotein C that elicited CD8 C T cells in vitro that cross react against the HLA-A2-presented, melanoma-associated MART-1 [27][28][29][30][31][32][33][34][35] peptide epitope. 35 These data supported the strategic use of homologous, pathogen-derived peptides to break operational tolerance mechanisms and promote effective immunity against "self" TAA.…”
Section: Discussionmentioning
confidence: 99%
“…Poly I:C has been used with a self-peptide to induce chronic, severe pancreatitis in MRL͞ϩ mice (11,12). Previous studies in mice have demonstrated that poly I:C caused a mild liver injury and inhibited liver regeneration (13,14).…”
Section: Ipopolysaccharide (Lps)͞d-galactosamine (D-galn)-mentioning
confidence: 99%
“…Subcutaneous, intranasal, and intravenous insulin can either delay the onset or reduce the incidence of diabetes in animal models (Gotfredsen et al 1985, Daniel and Wegmann 1996, Zekzer et al 1997. Administration of the insulin peptide B:9-23 has been both provocative as well as preventive in mouse models (Moriyama et al 2002, Liu et al 2003, Stene et al 2004) depending on the genetic background. Since the peptide does not have the physiological activity of insulin, tolerance induction might be the mechanism of disease prevention with B:9-23.…”
Section: Prevention Of Disease By Insulinmentioning
confidence: 99%